If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 8)(2x + 4)(3x + -6) = 0 Reorder the terms: (8 + x)(2x + 4)(3x + -6) = 0 Reorder the terms: (8 + x)(4 + 2x)(3x + -6) = 0 Reorder the terms: (8 + x)(4 + 2x)(-6 + 3x) = 0 Multiply (8 + x) * (4 + 2x) (8(4 + 2x) + x(4 + 2x))(-6 + 3x) = 0 ((4 * 8 + 2x * 8) + x(4 + 2x))(-6 + 3x) = 0 ((32 + 16x) + x(4 + 2x))(-6 + 3x) = 0 (32 + 16x + (4 * x + 2x * x))(-6 + 3x) = 0 (32 + 16x + (4x + 2x2))(-6 + 3x) = 0 Combine like terms: 16x + 4x = 20x (32 + 20x + 2x2)(-6 + 3x) = 0 Multiply (32 + 20x + 2x2) * (-6 + 3x) (32(-6 + 3x) + 20x * (-6 + 3x) + 2x2 * (-6 + 3x)) = 0 ((-6 * 32 + 3x * 32) + 20x * (-6 + 3x) + 2x2 * (-6 + 3x)) = 0 ((-192 + 96x) + 20x * (-6 + 3x) + 2x2 * (-6 + 3x)) = 0 (-192 + 96x + (-6 * 20x + 3x * 20x) + 2x2 * (-6 + 3x)) = 0 (-192 + 96x + (-120x + 60x2) + 2x2 * (-6 + 3x)) = 0 (-192 + 96x + -120x + 60x2 + (-6 * 2x2 + 3x * 2x2)) = 0 (-192 + 96x + -120x + 60x2 + (-12x2 + 6x3)) = 0 Combine like terms: 96x + -120x = -24x (-192 + -24x + 60x2 + -12x2 + 6x3) = 0 Combine like terms: 60x2 + -12x2 = 48x2 (-192 + -24x + 48x2 + 6x3) = 0 Solving -192 + -24x + 48x2 + 6x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6'. 6(-32 + -4x + 8x2 + x3) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-32 + -4x + 8x2 + x3)' equal to zero and attempt to solve: Simplifying -32 + -4x + 8x2 + x3 = 0 Solving -32 + -4x + 8x2 + x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 50x+50x=300 | | 5x+5-5= | | .05(2t-6)=.10(t+4)-.70 | | -4-3(t-5)= | | 2(x-6)=36 | | 8(z+8)= | | 25=45b | | -7+y=34 | | 4(x+2)+2=7x-3(x-2) | | -93=-1 | | tanx-3cotx=0 | | .6x+.7=.9x-.8 | | x+5x+2x=80 | | 30=r-17 | | 10xy=120 | | 4x+-93=-1 | | 1s+1p=15.65 | | 0.8=0.6+x-0.6x | | 64-32x=55-25x | | 3x+2+2x+5=22 | | S-15=12 | | 0.666666667x+3=0.6 | | 0.6+0.7=0.9x-0.8 | | -7c=-35 | | 10+m=13 | | 8x-6-3x+3=2 | | 4(y-3)=6y-12 | | n[n+1]+3=45 | | 2a=9a+14 | | 7-x=1(5-x) | | .12-0.02(x+2)=-0.02(2-x) | | 10x-4x+4+2=36 |